The role of the history of coronary heart disease among second degree relatives for predicting coronary artery disease - Saeed Alipour Parsa; Farzam Saemifar; Isa Khaheshi; Mohammadreza Naderian (Publisher: Shahid Beheshti University of Medical Sciences, 2016)
Introduction: The history of atherosclerotic disease among second degree family members of patients as a risk factor has not been properly explained. The present study aimed to assess this role in the Iranian population.Methods: This case-control study was performed on 500 consecutive patients, who were candidates for coronary angiography. The presence of Coronary Heart Disease (CHD) history among first and second degree relatives were determined by interviewing the participants.Results: In total, 450 patients were shown to have CHD as the case group and 50 without CHD as the control group. Family history of CHD among first degree relatives was 39.1% for cases and 22.0% for the controls with a significant difference (P = 0.018), however the history of CHD among second degree relatives was not statistically different in the case group and the control group (17.8% vs. 8.0%, P = 0.079). In total, 80 patients had CHD with simultaneous history of disease among their second degree relatives, while 370 with CHD had no history of disease among their second degree relatives. Our study could not find a significant difference between the two CHD groups with and without history of disease among second degree relatives in terms of cardiovascular risk profile.Conclusions: Despite the powerful effect of the presence of family history of CHD in first degree relatives on risk of CHD and its severity, the presence of this history among second degree relatives cannot predict the risk for CHD.